Juvenile Dermatomyositis in Pregnancy. (15th April 2013) - Madu, Anthony Emeka; Omih, Edwin; Baguley, Elaine; Lindow, Stephen W.
Abstract : Juvenile dermatomyositis has variable clinical presentations both in and outside of pregnancy. A literature review indicated that optimal maternal and fetal outcomes can be anticipated when the pregnancy is undertaken while the disease is in remission. Poorer outcomes are associated with flare-up of the disease in early pregnancy compared with exacerbation in the second or third trimester, when fetal prognosis is usually good. We present a case of JDM in pregnancy with disease exacerbation late in pregnancy and review of the relevant literature.